Adsorbent based on ion adsorption type rare earth tailings as well as preparation method and application of adsorbent

By covering MoS2 on the surface of rare earth tailings to form MoS2@RET adsorbent, the problems of low adsorption amount and poor selectivity of rare earth tailings are solved, efficient thorium recovery and environmental restoration are achieved, and the selectivity of thorium in rare earth ores is demonstrated. Ability to adsorption and multiple reuses.

CN119215847APending Publication Date: 2024-12-31XIAMEN INST OF RARE EARTH MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310778118.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the prior art, the adsorption amount of rare earth tailings is low and the selectivity is poor, making it difficult to effectively recover radioactive rare earth elements, especially thorium, resulting in environmental pollution and waste of resources.

Method used

MoS2 is coated on the surface of ion adsorption rare earth tailings for modification, and MoS2@RET adsorbent is formed, and its high specific surface area and mesoporous structure are used for selective adsorption of thorium.

Benefits of technology

It significantly improves the adsorption capacity to thorium, achieves a 99% removal rate, and remains efficient in multiple cycles, reducing costs and environmental pollution risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215847A_ABST
    Figure CN119215847A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of adsorbents, and relates to an adsorbent based on ion adsorption type rare earth tailings and a preparation method and application thereof.The adsorbent comprises the ion adsorption type rare earth tailings, the surfaces of the ion adsorption type rare earth tailings are coated with MoS2, and the MoS2 is bonded to the surfaces of the ion adsorption type rare earth tailings through chemical bonds. The MoS2 is coated on the surface of the ion adsorption type rare earth tailings for modification, the MoS2 (at) RET can be obtained through simple hydrothermal reaction, the raw materials are easy to obtain, the preparation method is simple, and the cost is relatively low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of adsorbents, and relates to an adsorbent based on ion-adsorbing rare earth tailings, a preparation method and an application thereof, and in particular to a method for preparing an adsorbent using ion-adsorbing rare earth tailings, and an application thereof in selectively recovering thorium from a radioactive rare earth waste residue leachate. Background Art

[0002] Ion-adsorption rare earth ore (IREO) is a mineral associated with natural radioactive elements. It is an important rare earth mineral resource in my country and a scarce mineral in the world. In the process of leaching rare earths, ion-adsorption rare earth ore will not only produce a large amount of rare earth tailings (RET), but also the radioactive elements may migrate, enrich and transfer to waste residues (IREORWR) and wastewater (IREORWW), forming radioactive pollutants. Th (thorium) is the main source of radiation. Its accumulation in soil and water will harm the ecological environment, affect biodiversity and ecological balance. In order to ensure the safety of production personnel and the health of the local environment, an effective IREORWR disposal method is urgently needed to reduce the hazards of radioactive sources.

[0003] Long-term storage of RET not only wastes resources, but also occupies land, causing geological disasters and environmental pollution. At present, the research on RET mainly focuses on the adsorption of rare earth elements. At the same time, some studies have explained the adsorption mechanism of rare earth ions on IREO, and there are few reports on radioactive nuclides. RET is a clay mineral with kaolin, quartz and halloysite as the main components. It has certain adsorption properties and is a cheap and easy-to-obtain natural adsorption material in mines. However, the low adsorption capacity and poor selectivity have greatly limited the utilization of tailings.

[0004] Some domestic scholars have reported on the adsorption behavior of IREO and RET: Guan et al. explored the mechanism of yttrium adsorption by ionic rare earth minerals and found that IREO adsorbs free Y through silicon-oxygen bonds. 3+ Zhou et al. used sulfuric acid to activate RET to adsorb La 3+ With Y 3+ , the results showed that RET had a higher adsorption capacity for heavy rare earths and impurity ions did not have a significant effect on the adsorption process. Wang et al. studied the re-adsorption of rare earth elements during IREO leaching. The experiment showed that the comprehensive properties of the ore were the main factors affecting the adsorption capacity of rare earth elements.

[0005] However, as the development of liquid fluoride thorium reactor (LFTR) approaches commercialization, thorium, as a potential nuclear energy source, its recycling and reuse can not only reduce the risk of harming the environment, but also is conducive to the rational use of thorium resources.

[0006] MoS 2It is a typical layered transition metal disulfide. Recent studies have found that MoS 2 With ultra-high specific surface area and adsorption capacity, MoS has excellent performance in the field of heavy metal adsorption. 2 The excellent performance as an efficient adsorbent is due to its unique two-dimensional structure and special element composition: MoS 2 There are abundant S atoms on the surface of the layered structure and transition metal Mo. Due to the good affinity between S and heavy metals, MoS 2 It has become a promising adsorbent for the removal of heavy metals. Many researchers have conducted related research. 2 Nanosheets for the removal and recovery of heavy metal Ag, Q. Wang et al. used nanoscale MoS2 sheets as adsorbents to remove Cd from water 2+ , 3D MoS 2 Composite aerogel, thermally modified MoS 2 Nanosheets have also been applied to Hg 2+ adsorption.

[0007] Clay minerals, as an excellent natural adsorbent, are widely used in the removal of heavy metals. By modifying clay minerals through acid-base treatment, surface coating, grafting treatment, intercalation, etc., clay minerals can have more specific adsorption functions in practical applications. The preparation of adsorbents by modifying clay minerals has been widely carried out at home and abroad: Adedayo Bello et al. used nano-zero-valent iron to modify kaolin to remove vanadium from aqueous solution; Hao Cui et al. used acid to treat attapulgite to adsorb mercury ions from aqueous solution; Shu-Zhen Li et al. used hydrated iron solution and sodium dodecyl sulfate solution to treat montmorillonite for the removal of copper and cobalt; LSKostenko et al. grafted methylaminopropyl (NHCH 3 Bent), aminopropyl (NH 2 Bent), ethylenediaminepropyl (En Bent) and diethylenetriaminepropyl (Dien Bent) groups are used to adsorb copper, lead and cadmium; V. Marjanovi'c et al. adsorbed Cr in aqueous solution by mercaptosilane functionalization and acid activation of sepiolite 6+ .

[0008] At present, the research on RET mainly focuses on the adsorption of rare earth elements. At the same time, some studies have explained the adsorption mechanism of rare earth ions on IREO, and there are few reports on radionuclides. RET is a clay mineral with kaolin, quartz and halloysite as the main components. It has certain adsorption properties and is a cheap and readily available natural adsorption material in mines. However, its low adsorption capacity and poor selectivity have greatly limited the utilization of tailings. Summary of the invention

[0009] In order to improve the shortcomings of the prior art, the present invention adopts ion adsorption type rare earth tailings and coats its surface with MoS 2 Modification and application in the selective adsorption of thorium in radioactive residues provides a new idea for the high-quality utilization of rare earth tailings and the recovery of radioactive elements associated with rare earth mines.

[0010] In a first aspect, the present invention provides an adsorbent based on ion-adsorbing rare earth tailings, the adsorbent comprises ion-adsorbing rare earth tailings, the surface of the ion-adsorbing rare earth tailings is coated with MoS 2 .

[0011] According to an embodiment of the present invention, the MoS 2 Evenly coated on the surface of ion-adsorption rare earth tailings.

[0012] According to an embodiment of the present invention, the MoS 2 Bonded to the surface of ion-adsorbing rare earth tailings through chemical bonds.

[0013] According to an embodiment of the present invention, the adsorbent has a cluster structure, preferably, similar to MoS 2 The present flower cluster structure.

[0014] According to an embodiment of the present invention, the specific surface area of ​​the adsorbent is ≥ 6.290 m 2 / g-15.044m 2 / g, preferably the specific surface area of ​​the adsorbent is ≥8.203m 2 / g, for example, 8.203m 2 / g.

[0015] According to an embodiment of the present invention, the adsorbent has a mesoporous structure.

[0016] According to an embodiment of the present invention, the total pore volume of the adsorbent is ≥ 0.03402 cm 3 / g, preferably the total pore volume of the adsorbent is ≥ 0.05709 cm 3 / g, for example, 0.05651cm 3 / g.

[0017] In a second aspect, the present invention provides a method for preparing the above-mentioned adsorbent, comprising the following steps:

[0018] Soluble Mo salt, S salt and RET are mixed in a solvent, heated to 150-250°C and reacted for 3-10 hours to obtain MoS 2 @RET adsorbent.

[0019] According to an embodiment of the present invention, the soluble Mo salt is selected from at least one of sodium molybdate, lithium molybdate, ammonium molybdate or a hydrate thereof, for example, 6Mo 7 O 24 ·4H 2 O.

[0020] According to an embodiment of the present invention, the soluble sulfur salt is selected from at least one of thiourea; carbon disulfide, for example, CH 4 N 2 S.

[0021] According to an embodiment of the present invention, the solvent is selected from water.

[0022] According to an embodiment of the present invention, after the mixing and before the heating, the following step is further included: dispersing the mixed solution, and preferably the dispersing method is selected from ultrasound, stirring or other common methods in the art.

[0023] For example, the mixed solution is treated under ultrasonic waves for 10 to 60 minutes, for example, for 30 minutes.

[0024] According to an embodiment of the present invention, the reaction temperature is 180-240°C, preferably the reaction temperature is 200-220°C, for example 210°C.

[0025] According to an embodiment of the present invention, the heating includes heating to 150-250° C. at a rate of 1-10° C. / min, preferably at a rate of 2-8° C. / min, for example, 5° C. / min.

[0026] According to an embodiment of the present invention, the reaction time is 4 to 8 hours, preferably the reaction time is 5 to 7 hours, for example 6 hours.

[0027] In a third aspect, the present invention also provides a use of the above-mentioned adsorbent in adsorbing and / or separating radioactive residues, such as adsorbing radioactive thorium.

[0028] In a fourth aspect, the present invention provides a method for separating radioactive residues by adsorption using the above-mentioned adsorbent, comprising the following steps: adding the above-mentioned adsorbent to a solution containing radioactive residues and mixing.

[0029] According to an embodiment of the present invention, the pH value of the solution containing radioactive residues is 0.5-4, preferably the pH value of the solution containing radioactive residues is 1-3.5, and further preferably, the pH value of the solution containing radioactive residues is 1.5-3, for example, 3.

[0030] According to an embodiment of the present invention, in the solution containing radioactive residues, the concentration of radioactive residues is 20-200 mg / L, preferably the concentration of radioactive residues is 50-150 mg / L, and further preferably, the concentration of radioactive residues is 80-120 mg / L, for example 100 mg / L.

[0031] According to an embodiment of the present invention, the amount of the adsorbent is 0.02-1.0 g / 10 mL, preferably the amount of the adsorbent is 0.03-0.1 g / 10 mL, and further preferably, the amount of the adsorbent is 0.04-0.08 g / 10 mL, for example, 0.06 g / 10 mL.

[0032] According to an embodiment of the present invention, the adsorption time is 0 to 200 min, preferably the adsorption time is 10 to 100 min, and further preferably, the adsorption time is 20 to 80 min, for example, 60 min.

[0033] According to an embodiment of the present invention, the adsorption is performed at room temperature.

[0034] In a fourth aspect, the present invention further provides a method for regenerating the above-mentioned adsorbent, comprising the following steps: adding the adsorbent having adsorbed radioactive residues into an eluent for elution to obtain a regenerated adsorbent.

[0035] According to an embodiment of the present invention, the eluent is selected from Na 2 EDTA solution, sodium citrate solution or HCl aqueous solution, such as Na 2 EDTA solution.

[0036] According to an embodiment of the present invention, the concentration of the eluent is 0.01-0.1 mol / L, preferably the concentration of the eluent is 0.02-0.06 mol / L, for example, 0.05 mol / L.

[0037] According to an embodiment of the present invention, the elution time is 10 to 200 min, preferably 20 to 150 min, for example 2 h.

[0038] Beneficial Effects

[0039] 1. The present invention coats the surface of ion adsorption type rare earth tailings with MoS 2 Modification can be performed by a simple hydrothermal reaction to obtain MoS 2 @RET, the raw materials are easily available, the preparation method is simple and the cost is low.

[0040] 2. MoS prepared by the present invention 2 @RET has a flower cluster structure on the surface, and there are two corresponding MoS 2The weight loss stages of phase transition and RET dehydrogenation are significantly delayed, indicating that the prepared MoS 2 @RET has good stability and MoS 2 @RET’s specific surface area is greater than or equal to 8.203m 2 / g, total pore volume greater than or equal to 0.03402cm 3 / g, significantly larger than MoS 2 At the same time, MoS 2 The nitrogen adsorption and desorption curves of @RET all conform to the type IV isotherm with H3 hysteresis, which is the main characteristic curve of the mesopores of clay adsorbents. There is no adsorption limitation in the region of relatively high relative pressure.

[0041] 3. The inventor unexpectedly discovered that the prepared MoS 2 @RET has good adsorption capacity for radioactive ions, especially Th(IV), and can selectively adsorb Th(IV) from mixed solutions of radioactive ions, thereby effectively removing Th(IV) from the environment.

[0042] 4. MoS prepared by the present invention 2 @RET can not only undergo electrostatic adsorption with Th(IV), but also undergo chemical bonding and redox reactions, thereby selectively adsorbing Th(IV). However, it cannot selectively adsorb La(III), Eu(III), Lu(III), and Y(III), which have similar structures and properties to Th(IV).

[0043] 5. MoS prepared by the present invention 2 @RET, a high removal rate of 99% of Th(IV) can still be achieved in an environment with high concentrations of REs. Therefore, it has good application prospects in the remediation of real polluted wastewater and the selective removal of radionuclides.

[0044] 6. MoS of the present invention 2 @RET, after multiple cycles of adsorption and desorption, the removal efficiency of Th(IV) is still greater than 80%, so MoS 2 @RET can be reused many times, with low cost; at the same time, when in use, MoS 2 @RET is used as an adsorbent and mixed with a solution containing Th(IV) and then left to stand. The operation is simple and does not use volatile organic solvents, making it more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 RET and MoS prepared in Examples 1 and 2 of the present invention 2 @RET’s SEM image;

[0046] Figure 2 E is RET and MoS prepared in Examples 1 and 2 of the present invention. 2 @RET's thermogravimetric curve; Figure 2 F is RET and MoS prepared in Examples 1 and 2 of the present invention. 2 @RET’s XRD pattern;

[0047] Figure 3 G is RET and MoS prepared in Examples 1 and 2 of the present invention. 2 @RET’s FT-IR spectrum; Figure 3 H is RET, MoS prepared in Examples 1 and 2 of the present invention. 2 @RET’s nitrogen adsorption-desorption curve;

[0048] Figure 4 RET and MoS prepared in Examples 1-3 of the present invention 2 @RET、MoS 2 XPS spectrum of

[0049] Figure 5 RET and MoS prepared in Examples 1 and 2 of the present invention 2 @RET adsorption comparison under the same conditions;

[0050] Figure 6 MoS 2 @RET removal efficiency of Th(IV) at different pH, contact time, dosage and initial test concentration;

[0051] Figure 7 MoS 2 @RET adsorption capacity of La, Eu, Lu, and Y at different pH, contact time, dosage, and initial test concentration;

[0052] Figure 8 A is MoS 2 @Pseudo first-order kinetic model of Th(IV) adsorption by RET, Figure 8 B is MoS 2 @Pseudo-second-order kinetic model of Th(IV) adsorption by RET, Figure 8 C is MoS 2 @RET Elovich equation for Th(IV) adsorption, Figure 8 D is MoS 2 @RET Intraparticle diffusion equation for adsorbed Th(IV);

[0053] Fig. 9 For (IV) in MoS 2 @Adsorption isotherm on RET;

[0054] Fig.10 MoS 2 @Removal efficiency of Th(IV) by RET in four desorption and adsorption cycles;

[0055] Fig.11 To prepare MoS 2 @Schematic diagram of RET and its adsorption of rare earth ions;

[0056] Fig.12 MoS 2 @RET Bar graph of different ions recovered from radioactive waste residue leachate;

[0057] Fig.13 AMoS 2 @SEM image of RET after thorium adsorption, Fig.13 BH is MoS 2 @EDS spectrum of RET after thorium adsorption;

[0058] Fig.14 MoS 2 @RET element spectrum after thorium adsorption;

[0059] Fig.15 MoS 2 @XPS spectra of RET before and after thorium adsorption;

[0060] Fig.16 MoS 2 @RET XRD pattern before and after thorium adsorption. DETAILED DESCRIPTION

[0061] The adsorbent of the present invention, its preparation method and application will be further described in detail below in conjunction with specific examples. It should be understood that the following examples are only for illustrative purposes and explanation of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies realized based on the above content of the present invention are included in the scope of protection of the present invention.

[0062] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0063] The materials and their sources used in the following examples are as follows:

[0064] Ion adsorption rare earth ores (IREO) were collected from Xingguo County, Jiangxi Province, China; waste residues (IREORWR) were collected from Longnan County, Ganzhou City, China; LaCl 3 、EuCl 3 、LuCl 3 , YCl 3 ThCl 4Obtained by dissolving the corresponding rare earth oxide (REO) in HCl and hydrolyzing Th; 6Mo 7 O 24 ·4H 2 O、CH 4 N 2 S, (NH 4 ) 2 SO 4 Purchased from Shanghai Adamas Reagent Co., Ltd. 2 EDTA was purchased from Sinopharm Chemical Reagent Co., Ltd. All of the above drugs were of analytical grade and did not require further purification when used.

[0065] The materials prepared in the following examples were characterized using the following instruments and methods:

[0066] The morphology and elemental analysis of the materials were investigated by field emission scanning electron microscopy and EDS spectrometer (Thermo Fisher Scientific Apreo SLoVac). The synthesized materials were investigated by FTIR spectrometer (Nicolet iS 50) at 500–4000 cm -1 Fourier transform infrared (FTIR) spectroscopy was performed in the range of 2θ to 80°; scanning electron microscopy (SEM) was performed on an Apreo S LoVac instrument to study the microstructure of the samples; X-ray diffraction (XRD) was performed on a Miniflex 600 X-ray diffractometer with a Cu target irradiated in the 2θ range of 5° to 80°; the thermogravimetric curves of the samples were measured using a Mettler Telodo TGA / DSC 1 thermogravimetric and synchronous thermal analyzer; ICP-OES (Horiba Jobin Yvon SAS) was used to determine the RE in the solution S , Th, Al, Ca, and Mg concentrations; Axis Supra X-ray photoelectron spectroscopy (XPS) was used to analyze the concentration of Th in MoS 2 Adsorption behavior on @RET composites.

[0067] Example 1 Preparation of RET and MoS 2 With MoS 2 @RET Preparation

[0068] The ion-adsorbing rare earth mineral IREO was treated with 2% (NH 4 ) 2 SO 4 Soak in water solution for 48 hours to remove the existing ion adsorption form RE S , and then rinsed with deionized water, filtered, dried, and ground to pass through a 200-mesh sieve to obtain ion-adsorption rare earth tailings (RET).

[0069] Example 2 Preparation of MoS2 @RET

[0070] 1.24 g (NH 4 )6Mo 7 O 24 ·4H 2 O and 1.07 g CH 4 N 2 S was dissolved in 60 mL of deionized water and ultrasonicated until completely dissolved. 1 g of RET prepared in Example 1 was added to obtain a mixed solution. The mixed solution was then treated with ultrasound for 30 minutes to ensure that RET was fully dispersed in the solution. The dispersion was transferred to a 100 ml PPL-lined hydrothermal reactor and heated from room temperature to 210 °C at a rate of 5 °C / min for 6 hours. The product was cooled at room temperature, washed with deionized water 5 times, and then dried in a vacuum oven at 70 °C to obtain MoS 2 @RET.

[0071] Example 3 Preparation of MoS 2

[0072] In this example, except that RET was not added, the other reagents and methods were the same as those in Example 2 to prepare MoS 2 .

[0073] Example 4

[0074] 1.24 g (NH 4 )6Mo 7 O 24 ·4H 2 O and 0.40 g CH 4 N 2 S was dissolved in 60 mL of deionized water and ultrasonicated until completely dissolved. 1 g of RET prepared in Example 1 was added to obtain a mixed solution. The mixed solution was then treated with ultrasound for 30 minutes to ensure that RET was fully dispersed in the solution. The dispersion was transferred to a 100 ml PPL-lined hydrothermal reactor and heated from room temperature to 180 °C at a rate of 3 °C / min for 6 hours. The product was cooled at room temperature, washed with deionized water 5 times, and then dried in a vacuum oven at 70 °C to obtain MoS 2 @RET.

[0075] Example 5

[0076] 1.24 g (NH 4 )6Mo 7 O 24 ·4H 2 O and 1.07 g CH 4 N 2S was dissolved in 60 mL of deionized water and ultrasonicated until completely dissolved. 1 g of RET prepared in Example 1 was added to obtain a mixed solution. The mixed solution was then treated with ultrasound for 50 minutes to ensure that RET was fully dispersed in the solution. The dispersion was transferred to a 100 ml PPL-lined hydrothermal reactor and heated from room temperature to 210 °C at a rate of 5 °C / min for 10 hours. The product was cooled at room temperature, washed with deionized water 5 times, and then dried in a vacuum oven at 70 °C to obtain MoS 2 @RET.

[0077] Example 6

[0078] 1.24 g (NH 4 )6Mo 7 O 24 ·4H 2 O and 2.28 g CH 4 N 2 S was dissolved in 60 mL of deionized water and ultrasonicated until completely dissolved. 1 g of RET prepared in Example 1 was added to obtain a mixed solution. The mixed solution was then treated with ultrasound for 50 minutes to ensure that RET was fully dispersed in the solution. The dispersion was transferred to a 100 ml PPL-lined hydrothermal reactor and heated from room temperature to 220 °C at a rate of 6 °C / min for 12 hours. The product was cooled at room temperature, washed with deionized water 5 times, and then dried in a vacuum oven at 70 °C to obtain MoS 2 @RET.

[0079] Example 2: RET and MoS prepared 2 @RET’s characterization

[0080] like Figure 1 (A) and (B) are SEM images of RET. The morphology of RET is irregular and has a layered structure, and the particle size distribution is uneven. MoS 2 Under the microscopic view, it appears as a cluster of flowers, such as Figure 1 (C) and (D) show MoS 2 @RET SEM image of MoS after hydrothermal synthesis 2 @RET already has a relationship with MoS 2 Similar cluster structure.

[0081] See also Figure 2 (E) is MoS 2 @RET thermogravimetric curve, MoS 2 @RET has two obvious weight loss stages at 257-382℃ and 382-578℃, with relative weight reductions of 4.81% and 7.89%, respectively, corresponding to MoS 2The phase transition and the dehydroxylation process of RET, as well as the relative delay of the weightlessness stage, also explain the 2 @RET composite materials have better thermal stability.

[0082] Figure 2 (F) is the XRD comparison diagram before and after MoS2 modification, where 19.9°, 24.8°, 36.0°, 38.4°, and 62.3° correspond to the (001), (020), (002), (200), (113), and (060) crystal planes of kaolin in RET, respectively; 13.7°, 32.7°, and 57.8° correspond to the MoS 2 (002), (100) and (110) crystal planes; 20.9°, 26.7°, 60° are SiO 2 The (100), (011), and (121) crystal planes of quartz; 8.94° and 35.08° are the (001) and (110) crystal planes of halloysite. Figure 3 (G) shows RET, MoS 2 、MoS 2 @RET infrared absorption peak, 3693cm -1 With 3618cm -1 Corresponding to the stretching vibration peaks of the inner and outer hydroxyl groups in RET, 1700 cm -1 With 1437cm -1 Represents MoS 2 bending vibration peak. Figure 3 The nitrogen adsorption and desorption curves in (H) are consistent with H 3 The IV-type isotherm with type hysteresis is the main characteristic curve of the mesopores of clay adsorbents. There is no adsorption limitation in the region of relatively high relative pressure; MoS 2 @RET compared to MoS 2 The specific surface area and total pore volume increased. The above characterization proves that MoS 2 @RET, MoS 2 Successfully attached to the RET surface.

[0083] To further understand the interaction between MoS2 and RET, 2 @RET and MoS 2 Conduct XPS test analysis, Figure 4 (A) is RET, MoS 2 、MoS 2 @RET's XPS spectrum shows that in MoS 2 Elements such as Mo, S, Al, Si, O, and C appeared on @RET, which is consistent with the test results of SEM, XRD, FT-IR, etc. Figure 4(B)-(D) are high-resolution spectra of Al2p, O1s, and Si2p. After modification with MoS2, the relative signal contribution is weakened, indicating that there is an interaction between MoS2 and RET, rather than a physical mixture. Figure 4 (E) is the high-resolution spectrum of S2p, 160.24 eV and 161.59 eV correspond to MoS 2 In S 2p3 / 2 and S 2p1 / 2, it can be seen that there is an obvious chemical shift after the material is composited, and there is also a decreasing trend in 4(F)Mo3d, which further proves that there is a chemical bond between MoS2 and RET. It is worth mentioning that the weak peak at 167.80 eV corresponds to S 2 2- Indicates S 2- Partial oxidation is present.

[0084] Experimental Example 1 Adsorption Experiment

[0085] The adsorption experiment was carried out in a polyethylene centrifuge tube. The MoS prepared in Example 2 2 @RET adsorbent immersed in LaCl 3 、EuCl 3 、LuCl 3 , YCl 3 ThCl 4 Mixed solution (mixed solution LaCl 3 、EuCl 3 、LuCl 3 , YCl 3 ThCl 4 The initial test concentration of the mixed solution, the amount of adsorbent, the initial test pH value and the contact time are shown in Table 1. After mixing as shown in Table 1, the mixture was shaken in a constant temperature air bath shaking box at 200 rpm for 120 minutes for adsorption.

[0086] Table 1 Experimental conditions comparison table

[0087]

[0088] After adsorption, the supernatant was obtained by centrifugation at 4000 rpm for 1 min, and the adsorbent and the solution were separated using a 0.22 μm centrifuge tube and filtered and dried before characterization.

[0089] Among them, the adsorption capacity R of Th(IV) and the removal rate q e , distribution coefficient K d The adsorption separation factor SF is determined by formulas (1)-(4).

[0090]

[0091]

[0092]

[0093]

[0094] In formulas (1)-(4), C 0 and C e (mg / L) represents the initial concentration and equilibrium concentration of Th(IV) in the solution, V represents the volume of the mixed solution used for the adsorption study (ml), and m represents the mass of the adsorbent used (g).

[0095] The kinetic parameters were calculated using the pseudo-first-order kinetic model (Formula 5), ​​pseudo-second-order kinetic model (Formula 6), Elovich equation (Formula 7) and intraparticle diffusion model (Formula 8). 2 When it is close to 1, the closest kinetic model is used for calculation.

[0096] ln(q e -q t )=ln q e -k l t (5)

[0097]

[0098]

[0099] q t =kt 0.5 +C (8)

[0100] In formulas (5)-(8), q e and q t are the adsorption amounts of Th at equilibrium and time t, respectively, in mg / g; k 1 (min- 1 ) and k 2 (g·mg- 1 ·min- 1 ) are the first-order and second-order rate constants respectively; α(mg·g- 1 ·min- 1 ) and β (mg / g) are Elovich coefficients; k i (mg·g- 1 ·min- 1 / 2 ) and C (mg / g) represent the rate constant and constant of the intraparticle diffusion model, respectively.

[0101] Th(IV) adsorption isotherm MoS 2@RET was studied at 298 K and the experimental data were fitted by two widely used models, namely the Langmiur isotherm model (Eq. 9) and the Freundlich isotherm model (Eq. 10), to determine the potential relationship between the adsorption capacity and the equilibrium concentration of Th(IV).

[0102]

[0103]

[0104] In formulas (9)-(10), q e With q m are the adsorption capacity (mg / g) and maximum adsorption capacity at equilibrium concentration of Th(IV), Ce(mg / L) is the equilibrium concentration of Th(IV), KL is the Langmiur constant, Kf and n are the Freundlich constants.

[0105] In this test case, La, Eu, Lu, and Y are used to represent light, medium, and heavy rare earths to study the relationship between RET and MoS 2 @RET The selectivity of the two adsorbents for Th and REs. 3 、EuCl 3 、LuCl 3 , YCl 3 ThCl 4 The initial concentration was 100 mg / L, the contact time was 60 min, and the MoS 2 @RET was used at a dosage of 0.02 g and the results were as follows Figure 6 As shown in Figure 2, RET has a certain adsorption capacity for Th, and its adsorption capacity is 4.92 mg / g; MoS 2 The adsorption capacity of RET composite material for Th is increased by 6 times compared with RET, reaching 30.9 mg / g, which shows that RET is MoS 2 The uniform growth of MoS provides a basis for the improvement of Th(IV) adsorption under the premise of a small loss of rare earth ions. The adsorption performance comparison chart also shows that MoS 2 Compared with unmodified RET, @RET has significantly improved separation effects on La, Eu, and Lu, while the improvement in separation effect on Y is relatively small.

[0106] Effects of different factors on Th(IV) adsorption

[0107] The adsorption process of Th(IV) is affected by many factors, such as pH value, contact time, adsorbent dosage, initial concentration, etc. In order to obtain the best experimental conditions, the experiment was carried out under the conditions that La, Eu, Lu, Y and Th coexisted and the ion concentration was equal (in the initial concentration, the ion concentration was set to 20, 50, 100, 150, 200 mg / L in turn; in the pH value, contact time, and adsorbent dosage, the ion concentration was set to 100 mg / L).

[0108] Figure 6 (A) shows the removal rate and adsorption capacity of Th(IV) under different pH conditions. As the pH value increases from 0.5 to 3, the removal rate and adsorption capacity of Th(IV) in the solution increase significantly. When the pH value increases further, the removal rate and adsorption capacity of Th(IV) in the solution decrease significantly. Figure 6 (A) It can be seen that at pH 3, there is a good separation effect between Th and Res; when the pH increases to 3.5, the adsorption amount decreases, which may be caused by the hydrolysis of Th, resulting in a decrease in the ion concentration in the solution. It can be seen that under lower pH conditions, a large amount of H + Competitive adsorption with Th(IV) leads to MoS 2 @RET's adsorption capacity for Th(IV) decreased. With the increase of pH value, competitive adsorption decreased and the adsorption capacity increased significantly. 2 @RET shows excellent Th(IV) adsorption capacity in the pH range (1.5-3), see Figure 6 As shown in (B), when the contact time is 60 min, the removal rate of Th(IV) in the solution is close to 100%, which indicates that MoS 2 @RET exhibits a fast adsorption rate for Th(IV) in solution; see Figure 6 As shown in (C), as the amount of adsorbent increases from 0.02g to 0.1g, the removal rate gradually increases until Th(IV) is completely removed and the adsorption amount decreases, indicating that excessive dosage is not conducive to the dispersion of the adsorbent in the solution. The optimal dosage is 0.06g, at which time the removal rate reaches more than 99%; Figure 6 (D) It can be seen that with the increase of initial concentration, MoS 2 @The adsorption amount of RET gradually reached saturation.

[0109] Figure 6 In the figure, the black line represents MoS 2 @The relationship between the adsorption capacity of RET adsorbent for Th and pH value, contact time, adsorbent dosage, and initial concentration; the red line indicates MoS 2 @The relationship between the removal rate of Th by RET adsorbent and pH value, contact time, adsorbent dosage and initial concentration.

[0110] See also Figure 7 As shown in (E), MoS 2 @RET all showed good separation effects, but as the pH increased to 3.5, the separation effect decreased; see Figure 7 As can be seen in (F), the adsorption amount of coexisting rare earth ions did not increase significantly with the increase of contact time, which proves the application potential of MoS2@RET in separating Th and REs; Figure 7 (G) It can be seen that with the increase of Th(IV) concentration, MoS 2 The adsorption amount of @RET reached saturation, indicating that the amount of adsorbent is critical for the separation of Th and REs. Selecting the appropriate dosage can achieve a high removal rate while reducing the loss of rare earth ions. Figure 7 (H) shows that when the initial concentration is 100 mg / L, Th(IV) and REs(III) have a good separation effect. As the thorium ion concentration increases, the adsorption amount of Th(IV) gradually increases until saturation, but the adsorption amount of coexisting rare earth ions does not increase.

[0111] At the initial pH of 3, LaCl 3 、EuCl 3 、LuCl 3 , YCl 3 ThCl 4 The initial concentration was 100 mg / L, the contact time was 5 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, MoS 2 @RET was used in an adsorption condition of 0.02 g. Th(IV) was adsorbed on MoS 2 The adsorption kinetics model on @RET is as follows Figure 8 (A) The pseudo-first-order kinetic model, pseudo-second-order kinetic model, Elovich equation and intraparticle diffusion model were used to fit the experimental data to study the adsorption mechanism. The kinetic parameters are shown in Table 2. R 2 The higher correlation coefficient (0.99084) indicates that Th(IV) adsorbs on MoS 2 @RET is consistent with the pseudo-second-order kinetic model, which shows that Th(IV) in MoS 2 The adsorption on the @RET composite material is mainly chemical adsorption. The k obtained based on the pseudo second-order kinetic model 2 It is 0.003246802, and the equilibrium adsorption capacity is 32.404407 mg / g.

[0112] The Th(IV) in MoS was studied based on the Langmuir and Freundlich equations. 2@RET adsorption behavior, Fig. 9 The pH value is shown to be 3, and the adsorbent MoS 2 @RET usage is 0.02g, the volume of the mixed solution is 10mL, and the contact time is 60min. The Langmuir model and the Freundlich model adsorption isotherms show that the correlation coefficient of the Langmuir model is better than that of the Freundlich equation, which proves that the Langmuir model is more reasonable to describe the adsorption isotherm. 2 @RET adsorption isotherm parameters are shown in Table 3. K obtained by Langmuir model L The adsorption capacity of MoS is 18.89 L / mg, and the maximum adsorption capacity is 37.48 mg / g. 2 @RET composite materials have application prospects in the field of thorium and rare earth adsorption separation. (The parameters calculated by the two isotherm models are shown in Table 2)

[0113] Table 2 Th(IV) adsorption kinetic parameters

[0114]

[0115]

[0116] Table 3. Parameters of Langmuir and Freundlich isotherms

[0117]

[0118] Experimental Example 2 Regeneration Experiment

[0119] 0.06 g of MoS prepared in Example 2 was added 2 @RET was added to 10 ml (100 mg / L) Th, REs mixed solution and kept for 120 minutes for 4 desorption and adsorption cycles. 2 EDTA) solution (0.05 mol / L) to desorb MoS 2 @RET composite material 120min.

[0120] Cyclic performance is a key indicator for evaluating adsorbent performance. Fig.10 It shows that MoS 2 @RET shows the removal rate of Th(IV) after four cycles of adsorption and desorption. It can be seen that after four cycles, MoS 2 @RET still maintains a removal rate of 81.81%. However, during the cycle of the adsorbent, there will be a certain degree of loss, and the composition of the tailings is also very complex, so MoS 2A small amount of Mo may fall off during the cycle of @RET composite materials, which may be the reason for the decrease in removal efficiency after the first adsorption-desorption cycle. 2 EDTA enables efficient elution of Th(IV).

[0121] Application Example 1 Practical Application

[0122] Compared with solvent extraction, the adsorption method has the advantages of better environmental protection, high economy, simple operation, no use of volatile organic solvents, and relatively less acid and alkali consumption.

[0123] See also Fig.11 As shown, the use of MoS 2 @RET is a schematic diagram of the principle of adsorbing Th(IV) in the leachate of rare earth radioactive waste residue. The leachate of rare earth radioactive waste residue contains not only Th(IV) but also rare earth ions and other impurity ions. The leachate of rare earth radioactive waste residue used in this application example is taken from the slurry aging tank of a company factory in Longnan County, Jiangxi Province. It is mainly composed of a mixed leachate of impurity removal slag, acid-soluble slag and neutralization slag. Deionized water is added for dilution according to experimental requirements. The concentration is shown in Table 4. Fig.12 It shows that adding 0.06gMoS in 5ml of feed solution 2 @RET can achieve a high removal rate of 99.49% of Th(IV), while at higher concentrations of REs 3+ 、Al 3+ , Ca 2+ Mg 2+ Excellent selectivity is still maintained under the condition of coexistence.

[0124] Table 4. Actual ion concentration of feed solution

[0125]

[0126] Adsorption mechanism

[0127] RET, as a mining waste, is cheap and readily available and has abundant hydroxyl functional groups, which can be used as a catalyst for MoS 2 MoS2, as an excellent adsorbent, has many inherent sulfur sites and rich wrinkled nanosheet flower-like morphology. The soft Lewis acid-soft Lewis base interaction between heavy metal ions and S atoms in RET, MoS 2 Can enhance mass transfer and sufficient adsorption active sites.

[0128] To further understand MoS 2 @RET adsorption mechanism of thorium We have studied the adsorption mechanism of MoS 2 @RET conducted EDS, XPS, XRD and other analyses, see Fig.13 As shown in the figure, according to the results of the mapping scan, it can be seen intuitively that Th is evenly attached to the adsorbent surface and still maintains its original morphology. Fig.14 and Table 5, which shows that MoS 2 @RET contains elements, among which the standard mass composite ratio of S and Mo is close to the theoretical value. XPS is used to characterize MoS 2 @RET Surface chemical composition after thorium adsorption, MoS 2 XPS spectra of @RET before and after thorium adsorption Fig.15 In (A), Th signal appears. Fig.15 In the fine spectrum of (B), 333.69 eV and 343.00 eV correspond to Th 4f 7 / 2 and Th 4f 5 / 2, respectively, which clearly shows that thorium ions are adsorbed on MoS 2 @RET surface. Fig.15 In (C), the binding energies of S 2p3 / 2 and S 2p1 / 2 decreased from 159.29ev and 160.50ev to 158.77ev and 159.94ev, respectively. The relative contribution of S 2P signal decreased after thorium loading, which strongly indicates the presence of Th. 4+ ··S 2- interaction. Fig.16 MoS 2 @RET XRD diagram before and after thorium adsorption shows a new absorption peak at 30.9°, which also confirms that Th 4 + With S 2- There is a bonding effect between the H + and OH - Tends to attack S-Mo-S bonds, releasing SO during oxidation 4 2- Soluble substances such as thorium ions react with thorium ions to form insoluble compounds. 2 @RET's adsorption of thorium is the result of the combined effects of electrostatic interaction, chemical bonding, redox reaction and other mechanisms.

[0129] Table 5 Element weight percentage

[0130]

[0131] The present invention successfully prepared MoS by simple hydrothermal synthesis. 2 The particle-modified RET significantly improved the adsorption capacity of RET for Th(IV) and achieved the selective removal of Th(IV) from rare earths. The XRD, XPS, TG, FT-IR and other tests confirmed that MoS 2@RET nanocomposite material formation. The experimental conditions were optimized by operating parameters such as pH, contact time, adsorbent dosage, and initial concentration.

[0132] Adsorption and desorption experiments show that MoS 2 @RET has excellent selectivity, good adsorption performance and recyclability, and its adsorption process can be described by pseudo-second-order model and Langmuir isotherm model. In addition, the adsorption mechanism was studied in detail by XPS and XRD analysis and batch experiments, indicating that MoS 2 @RET's adsorption of thorium involves electrostatic interaction, chemical bonding, redox reaction and other mechanisms. As a theoretical verification, further exploration of the acid leaching solution of ionic rare earth mine radioactive waste residue found that MoS 2 @RET can still achieve a high removal rate of 99% of Th(IV) in an environment with high concentrations of REs. Experiments show that this MoS 2 @RET composites hold great promise for remediation of real-world contaminated wastewater and selective removal of radionuclides.

[0133] The above examples are used to illustrate the specific implementation of the present invention. However, the protection scope of the present invention is not limited to the above exemplary implementation. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the claims of the present invention.

Claims

1. An adsorbent based on ion adsorption type rare earth tailings, characterized in that: The adsorbent includes ion-adsorption type rare earth tailings, and the surface of the ion-adsorption type rare earth tailings is coated with MoS2. Preferably, the MoS2 is bonded to the surface of the ion-adsorption rare earth tailings through chemical bonds.

2. The adsorbent based on ion adsorption type rare earth tailings according to claim 1, characterized in that: The adsorbent has a mesoporous structure, and the specific surface area of ​​the adsorbent is ≥ 6.290 m 2 / g, the total pore volume of the adsorbent is ≥0.03402cm 3 / g.

3. A method for preparing the adsorbent according to claim 1 or 2, characterized in that: The steps include: Soluble Mo salt, S salt and RET are mixed in a solvent, heated to 150-250° C. and reacted for 3-10 hours to obtain a MoS2@RET adsorbent. Preferably, the soluble Mo salt is selected from at least one of sodium molybdate, lithium molybdate, ammonium molybdate or hydrates thereof, and the soluble S salt is selected from at least one of thiourea and carbon disulfide.

4. The preparation method according to claim 3, characterized in that: After the mixing and before the heating, the method further comprises the following step: dispersing the mixed solution.

5. The preparation method according to claim 3, characterized in that: The reaction temperature is 180-240°C. Preferably, the heating includes heating to 150-250° C. at a rate of 1-10° C. / min. Preferably, the reaction time is 4 to 8 hours.

6. Use of the adsorbent according to claim 1 or 2 or the adsorbent prepared by the method according to any one of claims 3 to 5 in adsorbing and / or separating radioactive residues, such as adsorbing radioactive thorium.

7. A method for separating radioactive residues by adsorption using the adsorbent according to claim 1 or 2 or the adsorbent prepared by the method according to any one of claims 3 to 5, characterized in that: The method comprises the following steps: adding the adsorbent into a solution containing radioactive residues and mixing the solution. Preferably, the pH value of the solution containing radioactive residues is 0.5-4.

8. A method for separating radioactive residues by adsorption according to claim 7, characterized in that: In the solution containing radioactive residues, the concentration of the radioactive residues is 20 to 200 mg / L. Preferably, the amount of the adsorbent used is 0.02 to 1.0 g / 10 mL. Preferably, the adsorption time is 0 to 200 min.

9. A method for regenerating the adsorbent according to claim 1 or 2 or the adsorbent prepared by the method according to any one of claims 3 to 5, characterized in that: The method comprises the following steps: adding an adsorbent having adsorbed radioactive residues into an eluent for elution to obtain a regenerated adsorbent.

10. The regeneration method according to claim 9, characterized in that: The eluent is selected from Na2EDTA solution, sodium citrate solution or HCl aqueous solution. Preferably, the concentration of the eluent is 0.01-0.1 mol / L. Preferably, the elution time is 10 to 200 minutes.